Morphometry Governs the Dynamics of a Drainage Basin: Analysis and Implications. (7th May 2014) - Biswas, Atrayee; Das Majumdar, Dipanjan; Banerjee, Sayandeep
Abstract : Mountainous rivers are the most significant source of water supply in the Himalayan provinces of India. The drainage basin dynamics of these rivers are controlled by the tectonomorphic parameters, which include both surface and subsurface characteristics of a basin. To understand the drainage basin dynamics and their usefulness in watershed prioritisation and management in terms of soil erosion studies and groundwater potential assessment and flood hazard risk reduction in mountainous rivers, morphometric analysis of a Himalayan River (Supin River) basin has been taken as a case study. The entire Supin River basin has been subdivided into 27 subwatersheds and 36 morphometric parameters have been calculated under four broad categories: drainage network, basin geometry, drainage texture, and relief characteristics, each of which is further grouped into five different clusters having similar morphometric properties. The various morphometric parameters have been correlated with each other to understand their underlying relationship and control over the basin hydrogeomorphology. The result thus generated provides adequate knowledge base required for decision making during strategic planning and delineation of prioritised hazard management zones in mountainous terrains.